2007
DOI: 10.1016/j.jfms.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects and outcome of feline permethrin spot-on poisonings reported to the Veterinary Poisons Information Service (VPIS), London

Abstract: Permethrin is a pyrethroid insecticide used in dermally applied spot-on flea treatments for dogs. Permethrin-based spot-on preparations are contraindicated in cats because of the high risk of toxicosis. The Veterinary Poisons Information Service (VPIS) is a 24-h access telephone service that provides veterinary professionals in the United Kingdom with information on the management of poisoned animals. In a review of 286 cases reported to the VPIS regarding inappropriate feline exposure to permethrin spot-on (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 4 publications
0
49
0
6
Order By: Relevance
“…Em relação aos inseticidas piretrinas e piretróides, foram observados somente casos de intoxicação em cães (7,1%). Entretanto, em estudo realizado por SUTTON et al (2007), foi observado que, em 1306 casos de intoxicação por permetrina, substância do grupo das piretrinas e piretróides, 80,9% das intoxicações ocorreram em gatos, e os autores atribuem esse fato às características anteriormente comentadas e relacionadas à dificuldade dos felinos em detoxificar algumas substâncias.…”
Section: Resultsunclassified
“…Em relação aos inseticidas piretrinas e piretróides, foram observados somente casos de intoxicação em cães (7,1%). Entretanto, em estudo realizado por SUTTON et al (2007), foi observado que, em 1306 casos de intoxicação por permetrina, substância do grupo das piretrinas e piretróides, 80,9% das intoxicações ocorreram em gatos, e os autores atribuem esse fato às características anteriormente comentadas e relacionadas à dificuldade dos felinos em detoxificar algumas substâncias.…”
Section: Resultsunclassified
“…It was found that PM is highly toxic to fish; but it is less toxic to guppies (Başer et al 2003). Likewise, Sutton et al (2007) reported that 96.9% of exposed cats developed clinical effects, 87.8% developed increased muscular activity and 10.5% of cases resulted in fatalities. PM was shown to induce DNA damage on rat heart cells (Vadhana et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Mesmo com os relatos sobre a baixa taxa de intoxicações pela via oral em mamíferos, devido a biotransformação do princípio ativo, que acontece no trato intestinal e hepático (NESKOVIC et al, 2013), algumas espécies podem apresentar dificuldade em metabolizar algumas substâncias tóxicas (SUTTON et al, 2007), podendo ser o caso dos coelhos.…”
Section: Relato De Casounclassified
“…Medeiros et al, (2009), ao analisarem 101 casos de intoxicação de cães e gatos atendidos na Policlínica Veterinária e no Hospital Veterinário da Universidade Fluminense, constataram que a cipermetrina foi responsável por 7,1% dos casos de intoxicação em cães. Já Sutton et al, (2007), observaram que de 286 felinos expostos a permetrina, 96,9% apresentaram sinais clínicos de intoxicação, com mortalidade de 10,5%.…”
Section: Introductionunclassified